Pemutakhiran Standar Operasional Prosedur (SOP) Siklus Penerimaan dan Pengeluaran Kas Pada Yayasan Al-Qoyyim Sukoharjo Jawa Tengah - Yuda,; Khairunnisa, Hera; Respati, Dwi Kismayanti (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study aims to provide suggestions for updating the Standard Operating Procedures (SOP) related to the income and expenditure cycle of the Al-Qoyyim Foundation in Sukoharjo. The sample of the research subjects was the Al-Qoyyim Foundation in Sukoharjo, Central Java, which is an institution engaged in social and humanitarian assistance. This study was conducted because the Standard Operating Procedures (SOP) implemented by the Al-Qoyyim Foundation in the form of spreadsheets and Microsoft Word were not equipped with adequate visual representations and had several shortcomings in their implementation, so that a more comprehensive SOP update was needed, namely an SOP with a flowchart. The research method used a qualitative method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as a design development framework. Research data were obtained through interviews or questionnaires and various documents and other reference sources. Data collection techniques were observation, interviews, and documentation. The results of the study show that the researcher has succeeded in compiling a proposal for updating the SOP for the cash receipt and disbursement cycle for the Al-Qoyyim Sukoharjo Foundation with an SOP format in the form of a flowchart which is expected to increase the efficiency of cash management, reduce the potential for irregularities, and guarantee the credibility of financial reports presented to donors and stakeholders.